Searching Gaia for extended structure in Globular Clusters. Issue Volume 14:Issue S351(2019) (May 2019) - Kuzma, Pete B.; Ferguson, Annette M. N.; Peñarrubia, Jorge
Abstract: A growing number of studies are revealing that many Milky Way globular clusters possess extended stellar structures beyond their traditional boundaries. Just how ubiquitous these structures are, and how they originate, are key questions to explore. In this contribution, we present a Bayesian technique that we have developed to separate probable members of globular clusters from the dominant Milky Way fore/background at large clustercentric radii and hence facilitate quantitative analyses of these intriguing structures. We demonstrate the promise of our method by showing how it recovers the known extended features around Palomar 5 and NGC 7089.